2015
DOI: 10.1016/j.rbre.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of grip strength in normal and obese Wistar rats submitted to swimming with overload after median nerve compression

Abstract: r e v b r a s r e u m a t o l . 2 0 1 5;5 5(1):43-47 REVISTA BRASILEIRA DE REUMATOLOGIA w w w . r e u m a t o l o g i a . c o m . b r a b s t r a c t Objective: To verify the functionality through muscle grip strength in animals with obesity induced by monosodium glutamate (MSG) and in control animals, which suffered compression of the right median nerve, and treated with swimming with overload.Methods: During the first five days of life, neonatal Wistar rats received subcutaneous injections of MSG. The contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Changes in this indicator can have both a central nature and indicate a violation of the energy metabolism processes in muscle tissue (Coradinia et al. ; Fujiwara et al. ; Martinez‐Huenchullan et al.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in this indicator can have both a central nature and indicate a violation of the energy metabolism processes in muscle tissue (Coradinia et al. ; Fujiwara et al. ; Martinez‐Huenchullan et al.…”
Section: Resultsmentioning
confidence: 99%
“…Coradini et al (2015) reported weak muscle strength in nerve compression model due to hypernociception [ 14 ]. Vitamin D is directly involved in muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…However, the swimming exercise with overload (10% of the BW) was not beneficial in promoting improvement in grip strength after median nerve crush. The swimming protocol had 3 weeks duration with 20, 30, and 40 min and it started 3 days after injury ( Coradinia et al, 2015 ). Already in an autologous nerve graft model a swimming protocol, 30 min 5 times a week without load did not present differences in both function and motor neuron number ( Andrade et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients’ age, site and degree of injury need to be considered ( Faroni et al, 2015 ; Panagopoulos et al, 2017 ). The sciatic nerve crush model is the most used in the experimental research on the neuromuscular regeneration and functional recovery after peripheral nerve crush injury ( Coradinia et al, 2015 ; de Moraes et al, 2018 ; Goulart et al, 2014 ; Ni et al, 2017 ; Teodori et al, 2011 ; Udina et al, 2011b ; Yang et al, 2015 ). However, many peripheral injuries in humans occur in the upper limb which makes the median nerve model clinically relevant ( Jager et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%